Cyclohexyl-Substituted Anthracene Derivatives for High Thermal Stability Organic Semiconductors - Dong, Yicai; Guo, Yuan; Zhang, Hantang; Shi, Yanjun; Zhang, Jing; Li, Haiyang; Liu, Jie; Lu, Xiuqiang; Yi, Yuanping; Li, Tao; Hu, Wenping; Jiang, Lang (Frontiers in Chemistry, 2019)
A novel p-type organic semiconductor with high thermal stability is developed by simply incorporating cyclohexyl substituted aryl groups into the 2,6-position of anthracene, namely 2,6-di(4-cyclohexylphenyl)anthracene (DcHPA), and a similar compound with linear alkyl chain, 2,6-di(4-n-hexylphenyl)anthracene (DnHPA), is also studied for comparison. DcHPA shows sublimation temperature around 360°C, and thin film field-effect transistors of DcHPA could maintain half of the original mobility value when heated up to 150°C. Corresponding DnHPA has sublimation temperature of 310°C and the performance of its thin film devices decreases by about 50% when heated to 80°C. The impressing thermal stability of the cyclohexyl substitution compounds might provide guidelines for developing organic electronic materials with high thermal stability.